Microfluidic Design for Continuous Separation of Blood Particles and Plasma Using Dielectrophoretic Force Principle - Pakhira, Writtick; Kumar, Rajagopal; Panwala, Fenil Chetankumar; Ibrahimi, Khalid Mohd (Computer Assisted Methods in Engineering and Science; Vol 30 No 3 (2023), 2023)
Nowadays, various microfluidic platforms are developed with a focus on point-of-care diagnostics in the biomedical field. Segregation of blood cells and plasma remains an essential part of medical diagnosis in which isolation of platelets (PLTs), red blood cells (RBCs), and white blood cells (WBCs) is a requirement for analysis of diseases associated with thrombocytopenia, anemia, and leukopenia. However, a separated plasma contains proteins, nucleic acids, and viruses, for which a microfluidic device is introduced for continuous separation of PLTs, RBCs, and WBCs with a diameter range of 1.8–2 µm, 5–6 µm, and 9.4–14 µm, respectively, and plasma using the negative dielectrophoresis (DEP) force principle. In this study, design of the device is explored utilizing COMSOL Multiphysics 5.4 tool. This design consists of triangular micro-tip electrodes at the top, which are effective in generating a nonuniform electrical field with a significantly small AC voltage. Furthermore, the blood cells are subjected to the negative DEP force resulting in deflection toward their respective outlets, due to which blood cell separation purity and efficiency from the sample, i.e., of PLTs, RBCs, and WBCs, improve and are obtained at a blood sample flow velocity of 700 µm/s and buffer solution flow velocity of 1200 µm/s with 12 V pp electrode voltage, after experimenting and testing at multiple flow velocities. Additionally, a curved microchannel is introduced, producing better plasma flow velocity than a flat microchannel at the side outlets (top and bottom). The cell-free diluted plasma is collected at side outlets (top and bottom) with high purity and improved separation efficiency.